Pengaruh Trust terhadap Impulsive Buying pada Kosumen Dewasa Awal Pengguna Live Streaming Shopping di Kota Padang - Rahayu, Nurmi Putri; Dwatra, Free Dirga (ARZUSIN, 2024)
This study aims to determine the influence of trust on impulsive buying in early adult consumers in making purchase through live streaming shopping in Padang. This study uses quantitative research design. The sample in this study amounted to 122 live streaming shopping users used the accidental sampling technique. The instrument of this research used Impulsive Buying Tendency scale and Trust scale. Simple linear regression analysis techniques are used in the processing of data. The analysis results obtained a value of R square = 0,126 with p = 0,000. Research results show that there is an influence of trust against impulsive buying on early adult consumers of live streaming shopping in Padang City. This proves that with the high level of trust in live streaming, the possibility that consumers will behave impulsively buying will be high anyway.